2021
DOI: 10.3390/s21062053
|View full text |Cite
|
Sign up to set email alerts
|

Risk Analysis by a Probabilistic Model of the Measurement Process

Abstract: The aim of the article is presentation of the testing methodology and results of examination the probabilistic model of the measurement process. The case study concerns the determination of the risk of an incorrect decision in the assessment of the compliance of products by measurement. Measurand is characterized by the generalized Rayleigh distribution. The model of the measurement process was tested in parallel mode by six risk metrics. An undesirable effect in the reconstruction building block of the model … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…In this research, based on the activities described, it was possible to propose measures to improve the hot rolling process. Knowledge of the organization and analytical methods were used [33]. Statistical analyses of the factors that may have caused the occurrence of rolled-in foreign material were performed to achieve the stated objective.…”
Section: Discussionmentioning
confidence: 99%
“…In this research, based on the activities described, it was possible to propose measures to improve the hot rolling process. Knowledge of the organization and analytical methods were used [33]. Statistical analyses of the factors that may have caused the occurrence of rolled-in foreign material were performed to achieve the stated objective.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, histograms can represent graphically this probability density function, and the guard bands help us to define if the item of interest meets a specified requirement. Finally, Bayes’ theorem can be used to estimate the risk of the consumer [ 36 ].…”
Section: Methodsmentioning
confidence: 99%
“…Recent studies have shown that risk assessment models can be compared using metrics relates to the confusion matrix [18,34]. Expressions for evaluating the global risk of producers and consumers from equations (28) and (31) are a kind of classifier that sorts measurements as falsely rejected (FR) and falsely accepted (FA), so that R P = FR and R C = FA. Considering that the measurements within the tolerance interval and the acceptance interval were defined as true positive (TP), and that the measurements outside the acceptance interval and tolerance interval were defined as true negative (TN), it is feasible to construct a confusion matrix [18].…”
Section: Comparison Of Models Using Metrics Related To the Confusion ...mentioning
confidence: 99%
“…Knowledge about these data is given by prior distribution, that is, by the probability density function (PDF), designated with g 0 (η) [13]. Depending on the available data, the prior can be a non-parametric, one-parameter, or two-parameter distribution [27,28]. According to the principle of maximum entropy (PME), if data for two moments are available, a two-parameter distribution is used for the prior [29][30][31].…”
Section: Introductionmentioning
confidence: 99%